2013
DOI: 10.2151/jmsj.2013-408
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nonuniform Beam Filling Effects by Vertical Decorrelation: Theory and Simulations

Abstract: Algorithms for estimating precipitation rates from spaceborne radar observations of apparent radar reflectivity depend on attenuation correction procedures. The algorithm suite for the Ku-band precipitation radar aboard the Tropical Rainfall Measuring Mission satellite is one such example. The well-known problem of nonuniform beam filling is a source of error in the estimates, especially in regions where intense deep convection occurs. The error is caused by unresolved horizontal variability in precipitation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…The presence of graupel or hail in the column and potentially unique low-level raindrop size distributions in such cases that could be systematically different from the ones assumed in 2A25 V7. Additionally, nonuniform beamfilling often results in underestimation of PIA (Kozu and Iguchi 1999;Short et al 2013). This is consistent with the presented results in that TRMM PR attenuation-corrected reflectivities are lower than WSR-88D reflectivities throughout most of the vertical column.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of graupel or hail in the column and potentially unique low-level raindrop size distributions in such cases that could be systematically different from the ones assumed in 2A25 V7. Additionally, nonuniform beamfilling often results in underestimation of PIA (Kozu and Iguchi 1999;Short et al 2013). This is consistent with the presented results in that TRMM PR attenuation-corrected reflectivities are lower than WSR-88D reflectivities throughout most of the vertical column.…”
Section: Discussionsupporting
confidence: 91%
“…With the highest PIA estimates being associated with the highest 1.5-km altitude reflectivities, and their increase with convective intensity, it is apparent that the extreme convective intensities and rain rates that are the focus in this study are prone to significant column-integrated attenuation. In addition to possible bias in the PIA estimate in conditions of very heavy precipitation and nonuniform beamfilling (Kozu and Iguchi 1999;Short et al 2013), another source of error lies in the assumed distribution of attenuation throughout the data column during the attenuation correction. The greater the PIA, the greater the potential for errors in attenuation-corrected reflectivity.…”
Section: Evaluation Of Trmm-retrieved Relationshipsmentioning
confidence: 99%
“…Thus, the rain attenuation correction of reflectivity is taken into account for SR by a combination of the surface reference technique and HB method. However, the non‐linear nature of radar attenuation equation and power law relations among specific attenuation, radar reflectivity, and precipitation rate is known to induce biases in PIA and thus bias in reflectivity retrieved (Short et al, 2013). Liao and Meneghini (2009) found that for stratiform rain, the TRMM‐PR attenuation correction is adequate, whereas it underestimates for convective rain events.…”
Section: Reflectivity Intercomparison Between Gr and Srmentioning
confidence: 99%
“…The large radar resolution volumes of spaceborne radars have two main drawbacks: first they smooth out the natural variability of the microphysical processes; second they may introduce biases induced by non-uniform beam filling (NUBF) effects. These effects are ubiquitous in space radar measurements and occur when large gradients of radar reflectivity are present within the field of view of the instrument: this can cause significant errors in the estimated microphysical properties [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%